Standby and Active Leakage current control and Insertion Power Network Synthesis - Chaithanya, Panem; Krishna, P. Prsanna Murali (International Journal of Computer Sciences and Engineering, 2014)
Leakage power has become a serious concern in nanometer CMOS technologies, and power-gating has shown to offer a viable solution to the problem with a small penalty in performance. This paper focuses on leakage power reduction through automatic insertion of sleep transistors for power-gating. In particular, we propose a novel, layout-aware methodology that facilitates sleep transistor insertion and virtual-ground routing on row-based layouts. We also introduce a clustering algorithm that is able to handle simultaneously timing and area constraints, and we extend it to the case of multi- sleep transistors to increase leakage savings. The results we have obtained on a set of benchmark circuits show that the leakage savings we can achieve are, by far, superior to those obtained using existing power-gating solutions and with much tighter timing and area constraints Leakage power is a major concern in sub-90-nm CMOS technology. The exponential increase in the leakage component of the total chip power can be attributed to threshold voltage scaling, which is essential to maintain high performance in active mode, since supply voltages are scaled. Numerous design techniques have been proposed to reduce standby leakage in digital circuits. Out of this rich set of solutions, power gating has proven to be a very effective approach to minimize standby leakage while keeping high speed in the active mode. It is based on the principle of adding devices, called sleep transistors in series to the pull-up and/or the pull-down of the logic gates, and turning them off when the circuit is idle, thereby decreasing the leakage component due to IDS sub-threshold currents. When an nMOS sleep transistor is used on the pull-down path, a SLEEP signal controls its active/standby mode.